Tip of Word-Making in \'Do Kalame- Harfe- Hesab\' by Kiumars Saberi - نعمت‌الله ایران‌زاده; نجمه زارع بنادکوکی (مطالعات زبانی و بلاغی)
Style owner Humorists uses special tips and possibilities for creating humor and critical thinking spirit in their open-minded audience especially professional readers of literary texts. One of these possibilities which is considered as characteristics of Kiumars Saberi&#39s style is word-making and term-making. In this paper it is attempted to investigate various aspects of this work in &#39Do kalame Harfe Hesab&#39 by Kiumars Saberi. We studied terms and words devised by Saberi in terms of construction and meaning and came to the conclusion that most of them are analogous words and they are usually a noun or adjective plus a prefix. In terms of meaning, words and terms are classified in four categories: parody words and terms (words that are made following the style of a ââfamous writer or poet), critical (criticism of the state, making the critique of new word-making) and lexical which are mostly surprising and fun and have less critical aspect. Another important point in word making by Saberi is change in meaning of some words and offering a new and humoristic interpretation for that word.